Encroachment on the sovereignty and independence of Ukraine by the russian federation - Shevchuk L. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Goal. In connection with the unprecedented attack of the Russian Federation on Ukraine, international treaties on peace were violated, the recognition of Ukraine by the world community as an independent, independent and democratic state as a whole. Therefore, the purpose of this article is to analyze the facts of Russia’s complete disregard for international treaties as evidence of a violation of any legal norms. After all, this means nothing more than the elimination of such legal principles as sovereignty, independence, integrity, inviolability, which in particular can lead to a violation of world order. Method. A certain analysis and generalization of scientific and theoretical material were carried out. The study followed such methods of scientific knowledge as comparative, analysis, and synthesis. Results. In the course of this study, an analysis of the facts was conducted to what extent the recklessness, shortsightedness, and arrogance of the interests of one state can lead to culminating and tragic consequences for the entire world community in particular. Scientific novelty. We need to understand that everything that is directly related to the sovereignty of the state, its independence, and especially when we see violations of the principles of integrity that are provided for by constitutional norms, then perhaps the novelty itself is relevant, if only for the reason that once again we observe when the factor of force abruptly exceeds the factor of law with the consequences of thousands of deaths. Practical significance. The results and conclusions of scientific research can be applied or taken into account in law enforcement practice and consulting.